Blame it on the WTO? : a human rights critique - Joseph, Sarah (Oxford : Oxford University Press, 2011)
The WTO is often accused of not paying enough attention to human rights. This book weighs these criticisms and examines their validity, both from a legal and from political and economic points of views. It asks whether the WTO is under an obligation to construct a fairer trade system and discusses suggestions for reform.
Includes bibliographical references and index.
Description based on print version record.
Keywords: World Trade Organization; Human rights; Foreign trade regulation